Clause analysis in two narrative types written by elementary school students - Rubio, Manuel (Árboles y Rizomas, 2020)
This article aims to compare both the type of clauses in narratives written by elementary school students and the degree of interdependency (parataxis and hypotaxis) and logico-semantic relations of clause complexes to identify the main changes observed as schooling progresses. The corpus consists of 180 texts produced by students of 3rd, 5th and 7th elementary levels under two writing conditions. Results indicate a significant predominance of clause complexes in the three elementary levels, with paratactic interdependency and logico-semantic relations of expansion conveyed by some circumstantial features and new information added through conjunctions. Nevertheless, an increased hypotactic relation pattern is observed. This pattern reaches significant levels when comparing texts written by 5th grade to 3rd grade students. It is concluded that students progressively advance by condensing information in the same syntagmatic structure. This means a qualitative change between 3rd and 5th elementary levels. In general, students write narratives which present actions as observable events, whose participants virtually do not talk neither reflect on their actions. However, there is an emerging trend to enrich their productions incorporating these aspects as they advance in schooling.